2008
DOI: 10.3732/ajb.95.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Scutifolium jordanicumgen. et sp. nov. (Cabombaceae), an aquatic fossil plant from the Lower Cretaceous of Jordan, and the relationships of related leaf fossils to living genera

Abstract: A new species of aquatic plant, Scutifolium jordanicum gen. et sp. nov., Taylor, Brenner & Basha, is described from the Albian of Jordan. The leaves are microphyllous with a symmetrical, elliptical to suborbiculate shape, convex to rounded apex and base, and actinodromous to palinactinodromous primary venation. The peltate, centrally attached petioles are narrow, elongate, and alternately arranged on similarly sized stems. The leaves appear to be thick and have aerenchyma. Comparisons to plants with centrally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…Thus, recognition of crown group fossils in the Aptian-Albian indirectly implies that these were aquatic plants, and this is confirmed by the vegetative morphology of Pluricarpellatia, Scutifolium, and Brasenites (Wang and Dilcher 2006;Taylor et al 2008;Friis et al 2011). …”
Section: Nymphaealesmentioning
confidence: 68%
See 3 more Smart Citations
“…Thus, recognition of crown group fossils in the Aptian-Albian indirectly implies that these were aquatic plants, and this is confirmed by the vegetative morphology of Pluricarpellatia, Scutifolium, and Brasenites (Wang and Dilcher 2006;Taylor et al 2008;Friis et al 2011). …”
Section: Nymphaealesmentioning
confidence: 68%
“…This was also noted by Taylor et al (2008), who concluded that Pluricarpellatia and Scutifolium were related to Cabombaceae, and by Friis et al (2011). Characters of the best-understood fossil, Monetianthus, do not make sense for a stem relative of Nymphaeales, since the most recent common ancestor of the order can be reconstructed as having hypogynous flowers and a smaller number of free carpels containing one ovule each (Endress and Doyle 2009).…”
Section: Nymphaealesmentioning
confidence: 92%
See 2 more Smart Citations
“…There is also evidence for major changes in fresh water ecosystems during the same period. An early invasion of angiosperms into the aquatic realm is indicated by several whole plant occurrences (Sun et al 2002;Friis et al 2003;Mohr et al 2008), isolated Brasenia-like floating leaves (Saporta 1894;Taylor et al 2008), and flowers and seeds related to the Nymphaeales (Friis et al 2009(Friis et al , 2011. Heterosporangiate ferns with inferred aquatic habit also became established and proliferated markedly during the Early Cretaceous (e.g.…”
mentioning
confidence: 99%